Tannin-based foams and methods and uses thereof

CN116814038BActive Publication Date: 2026-10-27NANJING FORESTRY UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310664082.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-06
Publication Date
2026-10-27
Estimated Expiration
2043-06-06

AI Technical Summary

Technical Problem

[0007]针对现有技术中单宁基泡沫材料的原料多采用原始单宁,发泡剂为乙醚、戊烷、己烷或氟利昂,不环保或具有可燃性,发泡过程中需添加酸性催化剂,导致的单宁基泡沫强度低,酸性催化剂污染环境的技术问题,本申请提供单宁基泡沫,成品具有更高的强度,对环境危害极小,且具有更好的隔热保温性能和更高的耐火等级

Benefits of technology

[0026]采用本发明提供的技术方案,与已有的公知技术相比,具有如下有益效果:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116814038B_ABST
    Figure CN116814038B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of heat-insulating and flame-retardant materials, and relates to tannin-based foam as well as a preparation method and application thereof. In view of the technical problems in the prior art that raw materials of the tannin-based foam material are mostly original tannin, a foaming agent is ethyl ether, pentane, hexane or freon, which is not environmentally friendly or flammable, an acidic catalyst needs to be added in the foaming process, and the tannin-based foam has low strength and pollutes the environment, the application provides tannin-based foam, which comprises tannin degradation products, a foaming agent, an aldehyde compound or a non-aldehyde compound, the tannin degradation products are prepared by photo-catalytic degradation, hydroxyl radical degradation or superoxide anion radical degradation of original condensed tannin, and the maximum formaldehyde binding capacity of the tannin degradation products is 0.9-1.3 g / g. The prepared tannin-based foam has higher strength, extremely small harm to the environment, and better heat-insulating and heat-preserving performance and higher fire resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of heat insulation and flame retardant materials technology, specifically relating to tannin-based foam, its preparation method, and its application. Background Technology

[0002] Tannin-based foam is a high-performance foam material with broad application potential in flame retardancy, thermal insulation, and lightweight composite materials. Tannin-based foam materials are typically prepared from tannins, formaldehyde, furfuryl alcohol, foaming agents, and acid catalysts. Its most notable characteristics are that its main raw materials are green and renewable, and it exhibits high flame retardant properties and low thermal conductivity.

[0003] Chinese invention patent application number 2021103662070, entitled "A Tannin Foam Material with Electromagnetic Shielding Function and Its Preparation Method", was filed on April 6, 2021. The disclosed raw material is tannin with a tannin content of ≥70%, the crosslinking agent includes but is not limited to formaldehyde, glyoxal and glutaraldehyde, the catalyst is p-toluenesulfonic acid, and after being mixed evenly with nano-conductive materials, it is injected into a polyurethane foam template and then calcined at high temperature to obtain a tannin foam material with electromagnetic shielding function. The foam material obtained by this method is actually a foam carbon material.

[0004] Chinese invention patent application number 2018110770665, entitled "A Vacuum Insulation Board with Tannin Foam as Core Material and Its Preparation Method," filed on September 15, 2018, discloses the following raw materials: tannin from Vitex negundo bark; crosslinking agent: furfuryl alcohol; formaldehyde; catalyst: one or more of concentrated hydrochloric acid, concentrated phosphoric acid, and p-toluenesulfonic acid; and foaming agent: n-pentane or anhydrous diethyl ether. Chinese invention patent application number 201611257636X, entitled "A Dioscorea tannin Adsorbent Foam Material and Its Preparation Method," filed on December 30, 2016, discloses the following raw material: dioscorea tannin; crosslinking agent: formaldehyde; catalyst: one of acetic acid, phosphoric acid, and hydrochloric acid; and foaming agent: one of diethyl ether, pentane, hexane, or Freon. Chinese invention patent application number 2014100782456, invention title: A Tannin-based Biomass Foam Material and Preparation Method, application date: March 5, 2014, disclosed raw material as tannin, crosslinking agent as furfuryl alcohol and formaldehyde, catalyst as p-toluenesulfonic acid, and foaming agent as diethyl ether, pentane, hexane or Freon series. There are also published reports: Liao Dongsen, Xu Yang, Li Jinxing, et al. Preparation and performance characterization of environmentally friendly tannin-furfuryl alcohol-glyoxal foam material [J]. Light Industry Science and Technology, 2022, 38(05):61-64; Liu Bowen, Li Xuehui, Zhou Yunxia, ​​et al. Preparation of tannin-furfuryl alcohol-glyoxal copolymerized resin foam [J]. Journal of Forestry Engineering, 2022, 7(04):107-114; Wu Xi, Deng Jianping, Luo Lingcong, et al. Preparation of tannin-based foam material of hardwood and its Mechanical properties [J]. Journal of Forestry and Environment, 2021, 41(02): 212-218; Li Jinxing, Xu Yang, Zhou Xiaojian, et al. Modification of tannin / furan foam plastics by three reagents [J]. Journal of Northwest Forestry University, 2020, 35(03): 218-223; Xu Yang, Li Bin, Zhou Xiaojian, et al. Study on preparation process of bayberry tannin foam [J]. Functional Materials, 2018, 49(10): 10117-10122, 10126. The content reported in the above literature is similar to that of the patent application. The specific common points include the use of tannin or raw tannin as raw materials, the foaming agent being ether, pentane, hexane or Freon, and the need to add an acidic catalyst during the foaming process. Using tannin or virgin tannin as raw materials will result in low foam strength due to the large molecular weight, wide reaction site distance, and large steric hindrance of tannin-based foams. Using ether, pentane, hexane, or Freon as foaming agents is not environmentally friendly or is flammable. Acidic catalysts need to be added during the foaming process, which can have adverse effects on the environment in which the foam material is used, such as corroding surrounding metals or concrete.

[0005] Chinese invention patent application number 2019107345000, entitled "An Ultrasonic-Assisted Photocatalytic Selective Degradation of Condensed Tannins and a Method for Controlling the Degradation Degree," filed on August 9, 2019, discloses an ultrasonic-assisted photocatalytic selective degradation of condensed tannins and a method for controlling the degradation degree. Another Chinese invention patent application, number 201910734125X, entitled "An Ultrasonic-Assisted Hydroxyl Radical Selective Degradation of Condensed Tannins and a Method for Controlling the Degradation Degree," filed on November 12, 2019, proposes a controllable degradation method for condensed tannins. The principle is that there is a corresponding relationship between the molecular weight of the condensed tannin and the amount of formaldehyde bound, and the degree of degradation can be controlled based on changes in the amount of formaldehyde bound. However, neither of these patents addresses the specific application of the degraded products. How to apply tannin degradation products to foam materials to address their low strength, insufficient flame retardancy, and environmental pollution during the preparation process is an urgent problem to be solved. Summary of the Invention

[0006] 1. The technical problem that the invention aims to solve

[0007] In view of the technical problems in existing tannin-based foam materials, which mostly use raw tannins as raw materials and ether, pentane, hexane or Freon as foaming agents, which are not environmentally friendly or flammable, and require the addition of acidic catalysts during the foaming process, resulting in low strength of tannin-based foam and environmental pollution from acidic catalysts, this application provides tannin-based foam with higher strength, minimal environmental harm, better thermal insulation performance and higher fire resistance rating.

[0008] 2. Technical Solution

[0009] To achieve the above objectives, the provided technical solution is as follows:

[0010] The tannin-based foam of the present invention comprises the following components: tannin degradation products, foaming agent, aldehyde compound or non-aldehyde compound;

[0011] The tannin degradation products are prepared by photocatalytic degradation, hydroxyl radical degradation or superoxide anion radical degradation of the original condensed tannins; the maximum formaldehyde binding capacity of the tannin degradation products is 0.9 to 1.3 g / g.

[0012] Furthermore, the aldehyde compound is formaldehyde, glyoxal, or furfural; the non-aldehyde compound is hexamethylenetetramine or furfuryl alcohol.

[0013] Furthermore, the foaming agent is a temperature-triggered foaming agent.

[0014] Furthermore, the temperature-triggered foaming agent is a hydrofluoroolefin.

[0015] Furthermore, the hydrofluoroolefins are trans-1-chloro-3,3,3-trifluoropropene (C3H2F3Cl), trans-1,3,3,3-tetrafluoropropene (C3H2F4), or cis-1,1,1,4,4,4-hexafluoro-2-butene (C4H2F6).

[0016] Furthermore, the original condensed tannin is one or more extracts from the following: black thorn bark, acacia bark, larch bark, shortleaf pine bark, spruce bark, hemlock bark, red root bark, Indian gooseberry bark, bayberry bark, mountain locust bark, casuarina bark, jacaranda bark, willow bark, red pine wood, ephedra root, sorrel root, grape pomace, or yam tuber.

[0017] Application of tannin-based foam: The tannin-based foam is used in the preparation of building thermal insulation materials or fireproof materials.

[0018] The preparation method of tannin-based foam includes the following steps:

[0019] The process includes dissolving tannin degradation products in water, placing them in a low-temperature environment to equilibrate with the ambient temperature (not exceeding 15°C) to obtain an aqueous solution of tannin degradation products.

[0020] The step includes mixing the aqueous solution of the tannin degradation product with an aldehyde compound or a non-aldehyde compound to obtain a mixed solution; the mixing temperature is ≤15℃.

[0021] The process includes mixing the mixed solution with a foaming agent, heating to trigger the foaming agent to boil and volatilize, and reacting the tannin degradation products with aldehyde compounds or non-aldehyde compounds to obtain the tannin-based foam.

[0022] The tannin degradation products are prepared by photocatalytic degradation, hydroxyl radical degradation or superoxide anion radical degradation of the original condensed tannins; the maximum formaldehyde binding capacity of the tannin degradation products is 0.9 to 1.3 g / g.

[0023] Furthermore, the heating method used is infrared or microwave.

[0024] Furthermore, during the heating operation, the temperature is ≥20℃.

[0025] 3. Beneficial effects

[0026] Compared with existing known technologies, the technical solution provided by this invention has the following beneficial effects:

[0027] (1) The tannin-based foam of the present invention comprises tannin degradation products, foaming agent, aldehyde compound or non-aldehyde compound. The tannin degradation products are prepared by photocatalytic degradation, hydroxyl radical degradation or superoxide anion radical degradation of the original condensed tannin. The maximum formaldehyde binding amount of the tannin degradation products is 0.9 to 1.3 g / g. The finished tannin-based foam has higher strength, minimal environmental harm, better thermal insulation performance and higher fire resistance.

[0028] (2) The method for preparing tannin-based foam of the present invention does not use acidic catalysts during the preparation process, the preparation process is simple and has little environmental pollution. Attached Figure Description

[0029] Figure 1 Electron micrographs of tannin-based foams prepared for the examples and comparative examples, wherein,

[0030] A. Tannin-based foam prepared in Comparative Example 1;

[0031] B. Tannin-based foam prepared in Comparative Example 2;

[0032] C. Tannin-based foam prepared in Comparative Example 3;

[0033] Tannin-based foam prepared in Comparative Example 4;

[0034] E. Tannin-based foam prepared in Example 1;

[0035] Tannin-based foam prepared in Example 2;

[0036] Tannin-based foam prepared in Example 3;

[0037] Tannin-based foam prepared in Example 4. Detailed Implementation

[0038] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0039] Example 1

[0040] The preparation method of the tannin-based foam in this embodiment is as follows:

[0041] The tannin degradation product of bayberry (with the highest formaldehyde binding capacity) after 4 hours of photocatalytic degradation had an average degree of polymerization of 3.90 (mDP=3.90) and a formaldehyde binding capacity of 1.28 g / g, and was named BT4. 30 g of BT4 was mixed with 6 g of water and mechanically stirred in an ice-water bath for 10 min. Then, 5.5 g of furfuryl alcohol and 3 g of trans-1-chloro-3,3,3-trifluoropropene were added, and stirring was continued until the mixture was homogeneous. The mixture was then placed under infrared irradiation until the temperature inside the mixture reached 20°C. Heating was then stopped, and the foaming agent was triggered to boil, and foaming began. The polymerization reaction of tannin and furfuryl alcohol occurred simultaneously. When the volume stopped increasing, furfuryl alcohol foam, which is the tannin degradation product, was obtained.

[0042] Comparative Example 1

[0043] The preparation method of the tannin-based foam in this comparative example is as follows:

[0044] The reactants were raw bayberry tannin (undegraded tannin), with an average degree of polymerization of 7.19 (mDP=7.19) and a formaldehyde binding amount of 0.31g / g, named BT0. 30g of BT0 was mixed with 6g of water and placed in an ice-water bath with mechanical stirring for 10min. Then, 7.4g of furfuryl alcohol and 3g of trans-1-chloro-3,3,3-trifluoropropene were added, and stirring was continued until the mixture was homogeneous. The mixture was then placed under infrared irradiation until the temperature inside the mixture reached 20℃. Heating was then stopped, and the foaming agent was triggered to boil, and foaming began. The polymerization reaction of tannin and furfuryl alcohol occurred simultaneously. Raw tannin furfuryl alcohol foam was obtained when the volume stopped increasing.

[0045] Table 1 shows a comparison of the properties of the tannin-based foams prepared in the examples and comparative examples.

[0046] Table 1 Comparison of various performance characteristics between Example 1 and Comparative Example 1 (electron microscopy images of foam are shown in Figures E and A)

[0047]

[0048] Example 2

[0049] The preparation method of the tannin-based foam in this embodiment is as follows:

[0050] The larch tannin degradation product (with the highest formaldehyde binding capacity) was obtained after 5 hours of hydroxyl radical degradation. At this time, the average degree of polymerization of the degradation product was 2.51 (mDP=2.51), and the formaldehyde binding capacity was 1.02 g / g, named LT5. 30 g of LT5 was mixed with 6 g of water and placed in an ice-water bath with mechanical stirring for 10 min. Then, 5.5 g of formaldehyde aqueous solution (concentration 37%) and 3 g of trans-1,3,3,3-tetrafluoropropylene were added, and stirring was continued until the mixture was homogeneous. The mixture was then placed under infrared irradiation until the temperature inside the mixture reached 30°C. Heating was then stopped, and the foaming agent was triggered to boil, and foaming began. The polymerization reaction of tannin and formaldehyde occurred simultaneously. When the volume stopped increasing, the tannin degradation product formaldehyde foam was obtained.

[0051] Comparative Example 2

[0052] The preparation method of the tannin-based foam in this comparative example is as follows:

[0053] The reactants were virgin larch tannin (undegraded tannin) with an average degree of polymerization of 8.12 (mDP=8.12) and a formaldehyde binding amount of 0.38g / g, named LT0. 30g of LT0 was mixed with 6g of water and placed in an ice-water bath with mechanical stirring for 10min. Then, 7.4g of formaldehyde aqueous solution (concentration 37%) and 3g of trans-1,3,3,3-tetrafluoropropylene were added, and stirring was continued until the mixture was homogeneous. The mixture was then placed under infrared irradiation until the temperature inside the mixture reached 30℃. Heating was then stopped, and the foaming agent was triggered to boil, and foaming began. The polymerization reaction of tannin and formaldehyde occurred simultaneously. When the volume stopped increasing, virgin tannin formaldehyde foam was obtained.

[0054] Table 2 shows a comparison of the properties of the tannin-based foams prepared in the examples and the comparative examples.

[0055] Table 2 Comparison of various performance characteristics between Example 2 and Comparative Example 2 (electron microscopy images of foam are shown in Figures F and B)

[0056]

[0057] Example 3

[0058] The preparation method of the tannin-based foam in this embodiment is as follows:

[0059] The tannin degradation product of black thorn tree (with the highest formaldehyde binding capacity) was obtained after 10 hours of superoxide anion free radical degradation. At this time, the average degree of polymerization of the degradation product was 2.37 (mDP=2.37), and the formaldehyde binding capacity was 1.11 g / g. It was named AT10. 30 g of AT10 was mixed with 6 g of water and placed in an ice-water bath and magnetically stirred for 10 min. Then, 5.5 g of glyoxal and 3 g of cis-1,1,1,4,4,4-hexafluoro-2-butene were added and stirred until the mixture was homogeneous. The mixture was then placed under microwave heating until the temperature of the mixture reached 40°C. Heating was then stopped, and the foaming agent was triggered to boil. Foaming began, and the polymerization reaction of tannin and glyoxal occurred simultaneously. When the volume stopped increasing, the tannin degradation product glyoxal foam was obtained.

[0060] Comparative Example 3

[0061] The preparation method of the tannin-based foam in this comparative example is as follows:

[0062] The reactants were virgin black thorn tannin (undegraded tannin), with an average degree of polymerization of 9.75 (mDP=9.75) and a formaldehyde binding amount of 0.35g / g, named AT0. 30g of AT0 was mixed with 6g of water and placed in an ice-water bath with magnetic stirring for 10min. Then, 7.4g of glyoxal and 3g of cis-1,1,1,4,4,4-hexafluoro-2-butene were added, and stirring was continued until the mixture was homogeneous. The mixture was then placed under microwave heating until the temperature inside the mixture reached 40℃. Heating was then stopped, and the foaming agent was triggered to boil, and foaming began. The polymerization reaction of tannin and glyoxal occurred simultaneously. When the volume stopped increasing, virgin tannin glyoxal foam was obtained.

[0063] Table 3 shows a comparison of the properties of the tannin-based foams prepared in the examples and the comparative examples.

[0064] Table 3 Comparison of various performance characteristics between Example 3 and Comparative Example 3 (electron microscopy images of foam are shown in Figures G and C)

[0065]

[0066] Example 4

[0067] The preparation method of the tannin-based foam in this embodiment is as follows:

[0068] The tannin degradation product from grape pomace after 6 hours of photocatalytic degradation (with the highest formaldehyde binding capacity) had an average degree of polymerization of 2.66 (mDP = 2.66) and a formaldehyde binding capacity of 1.21 g / g, and was named GT6. 30 g of GT6 was mixed with 6 g of water and placed in an ice-water bath with magnetic stirring for 10 min. Then, 5.5 g of hexamethylenetetramine and 3 g of trans-1-chloro-3,3,3-trifluoropropene were added, and stirring continued until homogeneous. The mixture was then placed under microwave heating until the temperature reached 20°C. Heating was stopped, and the foaming agent was triggered to boil, initiating foaming. The polymerization reaction of tannin and hexamethylenetetramine occurred simultaneously. The tannin degradation product, hexamethylenetetramine foam, was obtained when the volume stopped increasing.

[0069] Comparative Example 4

[0070] The preparation method of the tannin-based foam in this comparative example is as follows:

[0071] The reactants were undegraded grape pomace tannins with an average degree of polymerization of 9.89 (mDP = 9.89) and a formaldehyde binding capacity of 0.41 g / g, named GT0. 30 g of GT0 was mixed with 6 g of water and placed in an ice-water bath with magnetic stirring for 10 min. Then, 7.4 g of hexamethylenetetramine and 3 g of trans-1-chloro-3,3,3-trifluoropropene were added and stirred until homogeneous. The mixture was then placed under microwave heating until the temperature reached 20°C. Heating was then stopped, and the foaming agent was triggered to boil, and foaming began. The polymerization reaction of tannins and hexamethylenetetramine occurred simultaneously. When the volume stopped increasing, the original tannin hexamethylenetetramine foam was obtained.

[0072] Table 4 shows a comparison of the properties of the tannin-based foams prepared in the examples and the comparative examples.

[0073] Table 4 Comparison of various performance characteristics between Example 4 and Comparative Example 4 (electron microscopy images of foam are shown in Figures H and D)

[0074]

[0075] According to national regulations, thermal insulation materials are those with a thermal conductivity of less than 0.2 W / (m·K), while high-efficiency thermal insulation materials are those with a thermal conductivity of less than 0.05 W / (m·K). B1-grade flame-retardant materials typically refer to materials with a limiting oxygen index (LOI) greater than 32%. Therefore, tannin-based foam prepared from degradation products is an excellent thermal insulation and flame-retardant material. Moreover, without using acidic catalysts and with less aldehyde-based or non-aldehyde-based crosslinking agents, the properties of tannin-based foam prepared from degradation products are significantly improved compared to undegraded tannin-based foam.

Claims

1. Tannin-based foam, characterized in that: It contains the following components: tannin degradation products, foaming agents, aldehyde compounds or non-aldehyde compounds; The tannin degradation products are prepared from the original condensed tannins through photocatalytic degradation, hydroxyl radical degradation, or superoxide anion radical degradation; the maximum formaldehyde binding capacity of the tannin degradation products is 0.9~1.3 g / g; The aldehyde compound is formaldehyde, glyoxal, or furfural; the non-aldehyde compound is hexamethylenetetramine or furfuryl alcohol. The foaming agent is a temperature-triggered foaming agent; The temperature-triggered foaming agent is a hydrofluoroolefin.

2. The tannin-based foam according to claim 1, characterized in that: The hydrofluoroolefins are trans-1-chloro-3,3,3-trifluoropropene, trans-1,3,3,3-tetrafluoropropene, or cis-1,1,1,4,4,4-hexafluoro-2-butene.

3. The tannin-based foam according to any one of claims 1-2, characterized in that: The original condensed tannins are one or more extracts from the following: black thorn bark, acacia bark, larch bark, shortleaf pine bark, spruce bark, hemlock bark, red root bark, citrus bark, bayberry bark, mountain locust bark, casuarina bark, ailanthus bark, willow bark, red pine wood, ephedra root, sorrel root, grape pomace, or yam tuber.

4. The application of the tannin-based foam according to any one of claims 1-3, characterized in that: The tannin-based foam is used in the preparation of building thermal insulation materials or fireproof materials.

5. The method for preparing tannin-based foam according to any one of claims 1-3, characterized in that: Includes the following steps: The process includes dissolving tannin degradation products in water, placing them in a low-temperature environment to equilibrate with the ambient temperature (≤15℃) to obtain an aqueous solution of tannin degradation products. The step includes mixing the aqueous solution of the tannin degradation product with an aldehyde compound or a non-aldehyde compound to obtain a mixed solution; the mixing temperature is ≤15℃. The process includes mixing the mixed solution with a foaming agent, heating to trigger the foaming agent to boil and volatilize, and reacting the tannin degradation products with aldehyde compounds or non-aldehyde compounds to obtain the tannin-based foam. The tannin degradation products are prepared by photocatalytic degradation, hydroxyl radical degradation or superoxide anion radical degradation of the original condensed tannins; the maximum formaldehyde binding capacity of the tannin degradation products is 0.9~1.3 g / g.

6. The method for preparing tannin-based foam according to claim 5, characterized in that: The heating method used is infrared or microwave.

7. The method for preparing tannin-based foam according to claim 6, characterized in that: During the heating operation, the temperature is ≥20℃.

Citation Information

Patent Citations

  • Tannin-based biomass foam material and preparation method thereof

    CN104163904A

  • Vegetable tannin antibacterial agent with body structure as well as preparation method and application thereof

    CN112472693A